THE APPLICATION OF RESTORATIVE JUSTICE IN HANDLING CORRUPTION OFFENDERS AS AN EFFORT TO RECOVER STATE LOSSES - July Esther; Juznizar Sinaga; Jinner Sidauruk; Nelly Kapitarani Panggabean (Fakultas Hukum, Universitas Samudra, 2024)
Research conducted by the author found that there were conflicts in law. This conflict in law occurred between Jampidsus Circular Letter Number: B1113/F/FD.1/05/2010 concerning Priorities and Achievements in Handling Corruption Crime Case under Article 4 of Law Number 31 1999 concerning the Eradication of Corruption Crimes. Related with the return of state losses in the Jampidsus Circular Letter Number: B- 1113/F/FD.1/05/2010 concerning Priorities and Achievements in Handling of Corruption Crime Cases states that if it has recover state financial losses, especially related to case Corruption crimes with relatively small losses need to be considered not to be followed up, except those which are still going on, meanwhile in Article 4 of Law Number 31 of 1999 concerning The Eradication of Corruption Crimes states that returns. State losses do not eliminate the punishment of the perpetrator. The Restorative Justice approach is if the Prosecutor's Office feel that there is a loss to the state's finances caused by the action criminal corruption and have small or no financial losses in the big fish category, the Prosecutor's Office can ask to investigate and issued a statement stating that the investigation into criminal acts of corruption This was stopped because the alleged perpetrator had returned the loss state and be proactive in the process of recovering financial losses that country. This is what is called the role of the Prosecutor's Office in implementing it restorative justice approach in resolving criminal cases corruption. The aim of this research is to analyze the implementation of implementation the principle of Restorative Justice in the context of Restitution State Financial Losses in handling criminal acts of corruption based on Jampidsus Circular Letter Number: B1113/F/FD.1/05/2010 concerning Priorities and Achievements in Handling Corruption Crime Cases